Sedentary Habits and Their Detrimental Impact on Global Health: A Viewpoint - Singh, Charu; Bandre, Gulshan; Gajbe, Ujwal; Shrivastava, Saurabh; Tiwade, Yugeshwari; Bankar, Nandkishor; Moizuddin, Khwaja (National Journal of Community Medicine, 2024)
With limited areas where people can work out, an increase in sedentary work with the growing popularity of desk jobs and television and video devices, inactive lifestyles are becoming more and more common around the world. The objective of the current review is to explore the role of sedentary habits in the causation of different diseases and their impact on global health standards. Consequently, the associated health problems are becoming more serious. Inactivity has a significant influence on the human body in numerous ways. It disrupts lipolysis, transporter proteins, muscle glucose, the metabolic process, and lipoprotein lipase functionality. Prolonged sedentary behavior directly impacts the gravity, body weight balance, and can lead to fluid retention, obesity, and an increase in oxidative stress. An inactive lifestyle has a range of adverse impacts on our bodies, including a surge in all-cause mortality, coronary heart disease mortality, and the probability of contracting diseases like diabetes mellitus, hypertension, and dyslipidemia, in addition to physical ailments like arthralgia and osteoporosis, mental health issues like depression, and mental retardation. Consequently, to advance public health, we need to reduce sedentary practices and increase physical activity.